Application of Web Communication Relationship Management in Small and Medium Enterprises - I Budiarti; R Andrian; A W N Falah (Universitas Komputer Indonesia, 2021)
Small and Medium Enterprises (UKM) in Indonesia are still managed traditionally since the touch of information technology is not optimal. On the other hand, the number of customers or transactions made by UKM may no longer be of small value. One modern business approach is to pay attention to customer factors, not only before the transaction but also after the transaction. Applications in the field of information technology in this domain are called Customer Relationship Management (CRM). This research tries to develop a CRM model adapted to the community's culture and the SME business model in Indonesia and considers the penetration of information technology in general. The approach used is to use the Prototype model in which the system creation process is structured and has several stages that must be passed so that the information system becomes better and easier. The results show the small and medium businesses can make CRM simpler and more generic